Diseño y estudio de Cápsulas de Café para compostaje como modelo de negocio utilizando Café de la región (Innovation & Development in Engineering and Applied Science, 2021)
This project aims to establish a business model where care for the environment prevails and an opportunity is generated using raw materials from the region, such as organic coffee produced in different provinces of the country. It is presented as a product coffee capsules made with biodegradable material from plant origin in order that these are easy to compost at the end of their useful life. In this project, a conceptual design of the product was carried out with basic concepts of concurrent engineering where mechanical structure studies of the components, feasibility studies, manufacturing, assembly, assembly and market were applied, to achieve a competitive, reliable and above-mentioned product. all friendly with the environment. A system was developed for both product design as such and for packaging and packaging, finding feasibility of the idea and high business opportunities.